The association between serum lipid levels and colorectal cancer risk: A dose-response meta-analysis of 23 studies - Iman Elahi Vahed; Zahra Esmaili; Mina Pourhabib Mamaghani; Shohreh Farshid; Behina Salarian; Mobina Alamdari; Zahra Azimizadeh; Zahra Rastad; Hoda Radmard; Hossein Soltaninejad; Mohammad Rahmanian (PLoS ONE, 2025)
Background Colorectal cancer (CRC) ranks as the third most prevalent cancer globally and the second leading cause of cancer-related mortality. Based on recent studies, lipid levels may have a relationship with the risk of CRC. This meta-analysis aims to better understand the association between various serum lipids and CRC risk. Methods A comprehensive search was conducted in Web of Science, PubMed, and Scopus. This meta-analysis, including only prospective cohort studies, performed random-effects meta-analyses using the Restricted Maximum Likelihood (REML) model to assess the association between the highest versus lowest categories of serum triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoproteins (LDL) with the risk of CRC, primarily using hazard ratios (HR) as the effect size. Subgroup analyses (e.g., by tumor site, region, and risk of bias) and meta-regression analyses (e.g., for mean age, mean BMI, sex distribution, and duration of follow-up) were conducted to explore heterogeneity. Dose-response analyses were performed utilizing three model types. Results Following the screening of 27,278 articles, 23 articles have been included in this study finally. The associations between TG, TC, HDL, and LDL levels and the risk of CRC, colon, and rectum cancers were examined separately. Higher levels of TC were not significantly associated with the risk of CRC (HR = 1.08; 95% CI: 0.90–1.30; I2 = 50.55%; p = 0.4187) and colon cancer (HR = 1.08; 95% CI: 0.99–1.18; I2 = 35.57%; p = 0.0720), but were significantly associated with an increased risk of rectum cancer (HR = 1.19; 95% CI: 1.08–1.32; I2 = 28.36%; p = 0.0004). Higher levels of TG were associated with an increased hazard of CRC (HR 1.11; 95% CI: 1.044–1.18; I2 = 0.0%; p = 0.0008). For colon cancer, TG showed a marginally significant association (HR 1.23; 95% CI: 0.99–1.55; I2 = 52.0%; p = 0.0576). No significant association was found between TG levels and rectum cancer risk (HR 1.036; 95% CI: 0.69–1.56; I2 = 67.29%; p = 0.8674).Also, higher levels of HDL were not significantly associated with the risk of CRC (HR 0.93; 95% CI: 0.83–1.03; I2 = 28.8%; p = 0.1527), colon cancer (HR 0.94; 95% CI: 0.75–1.19; I2 = 0.0%; p = 0.6243), and rectum cancer (HR: 0.95; 95% CI: 0.66;1.37; I2 = 0.0%; p = 0.7888). For colon cancer, higher LDL level was not significantly associated with risk (HR 0.91; 95% CI: 0.60–1.37; p = 0.21; I2 = 37%; p = 6558). Accordingly quadratic and RCS models represented as lowest AIC for TC (p = 0.026), for TG (p = 0.004), for LDL (p = 0.942) and for HDL (p = 0.295). Conclusion Higher TG level was significantly associated with increased risk of CRC and showed a borderline association with colon cancer (HR 1.23, 95% CI 0.99–1.55; p = 0.0576), while TC, HDL, and LDL showed no significant associations with these cancers. For rectum cancer, higher TC was significantly linked to increased risk, whereas TG, HDL, and LDL showed no significant associations. Future research should prioritize longitudinal studies to investigate the mechanistic roles of hormones and the gut microbiota in modulating colorectal cancer risk, alongside multi-omics studies that integrate lipid metabolism with other biological variables such as inflammatory markers and genetic predispositions. These efforts could clarify causal pathways and inform targeted prevention strategies.